Composition, rhetoric, and disciplinarity - Malenczyk, Rita, 1959-; Miller-Cochran, Susan K.; Wardle, Elizabeth (Elizabeth Ann); Yancey, Kathleen Blake, 1950- (Logan : Utah State University Press, 2018)
As a discipline, can rhetoric and composition continue its historical commitment to pedagogy without sacrificing equal attention to other areas, such as research and theory? In this book, contributors address disagreements about what it means to be called a discipline rather than a profession or a field. -- Provided by publisher.
Mapping the turn to disciplinarity / Kathleen Blake Yancey -- My disciplinary history / Barry Maid -- Acknowledging disciplinary contributions / Rochelle Rodrigo and Susan Miller-Cochran -- Learning from Bruffee / Rita Malenczyk, Neal Lerner, and Elizabeth H. Boquet -- Classification and its discontents / Gwendolynne Reid and Carolyn R. Miller -- Understanding the nature of disciplinarity in terms of composition's values / Elizabeth Wardle and Doug Downs -- Discipline and profession / Kristine Hansen -- Embracing the virtue in our disciplinarity / Jennifer Helene Maher -- Disciplinarity and first year composition / Liane Robertson and Kara Taczak -- Writing, English, and a translingual model for composition / Christiane Donahue -- Shared landscapes, contested borders / Whitney Douglas, Heidi Estrem, Kelly Myers, and Dawn Shepherd -- The major in composition writing and rhetoric / Sandra Jamieson -- Rhetoric and composition studies and Latinxs' largest group / Jaime Armin Mejía -- Redefining disciplinarity in the current context of higher education / Doug Hesse -- Looking outward / Linda Adler-Kassner.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: English language -- Rhetoric -- Study and teaching (Higher); Composition (Language arts) -- Study and teaching (Higher); Universities and colleges -- Curricula; Academic writing -- Study and teaching; Enseignement universitaire -- Programmes d'études.; Écriture savante -- Étude et enseignement; LANGUAGE ARTS & DISCIPLINES -- Composition & Creative Writing; LANGUAGE ARTS & DISCIPLINES -- Rhetoric; REFERENCE -- Writing Skills; Academic writing -- Study and teaching; Composition (Language arts) -- Study and teaching (Higher); English language -- Rhetoric -- Study and teaching (Higher); Universities and colleges -- Curricula; Electronic book